DIGITAL COMPETENCE AND CAREER SELF-EFFICACY IN HIGHER EDUCATION: EVIDENCE FROM UNDERGRADUATE STUDENTS - I Komang Syahjaya Kartika Asta; I Gede Riana; Ida Bagus Ketut Surya; Ayu Desi Indrawati (Adisam Publisher, 2026)
The rapid digitalisation of the labour market has increased the demand for graduates who possess not only technical skills but also the confidence to manage career-related challenges. However, empirical evidence explaining how digital competence contributes to students’ career self-efficacy remains limited. This study aims to examine the effect of digital competence on career self-efficacy among undergraduate students. A quantitative cross-sectional design was employed, involving undergraduate management students selected through a multistage sampling technique. Data were collected using structured questionnaires measured on a Likert scale and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that digital competence has a positive and statistically significant effect on career self-efficacy. Students with higher levels of digital competence demonstrate greater confidence in performing career-related tasks, particularly those involving digital platforms such as online job search and professional communication. These findings suggest that digital competence not only enhances technical capability but also strengthens students’ confidence in navigating career development processes. This study concludes that improving digital competence is essential for enhancing students’ readiness and confidence in entering the digital labour market.